Progressive manufacturing : managing uncertainty while blazing a trail to success - Engineer, Soli J. (J. Ross Pub. ; Apics, 2005)
"Progressive Manufacturing provides common-sense solutions to the seemingly never-ending inventory, delivery, cost, productivity, quality, and profit woes faced by manufacturers and other organizations. This book delineates the three keystones essential to achieving any significant degree of success - people, products or services, and processes. It presents thought-provoking ideas and methods for simplifying and improving processes at every level. The author explores topics usually overlooked that are instrumental to achieving increased levels of success, such as work breakdown structure and improvement curve theory. This unique reference takes you beyond the tried-and-true status quo and provides innovative techniques that will help you continuously improve operational results and increase profits."--Jacket
Keywords: Manufacturing industries -- Management.; Production management.; Organizational change -- Management.; Manufacturing industries -- Technological innovations -- Management.; Manufacturing industries -- Quality control.; Organizational change.; elektronické knihy; electronic books